Visible-light-responsive NaBiO3/UiO-67 heterojunction with enhanced photocatalytic performance. (15th August 2022) - Liu, Shiwen; Ren, Ziying; Xu, Hao; Xing, Yonglei; Jin, Xiaoyong; Ni, Gang; Wang, Zhen
Abstract: Photocatalysts for the degradation of pollutants, including semiconductors and metal-organic frameworks (MOFs), are currently limited by poor visible-light response, high carrier recombination rate, and finite quantum efficiency. In this study, we fabricated a new heterojunction using NaBiO3 and the MOF, UiO-67, by a simple electrostatic self-assembly method to achieve enhanced photocatalytic performance. Under visible-light irradiation, the NaBiO3 /UiO-67 heterojunction exhibited better photocatalytic activity for tetracycline degradation than neat UiO-67 and NaBiO3 . Its high degradation efficiency (88.6%) can be attributed to the efficient separation of photoinduced carriers, as evidenced by the results from photocurrent result, electrochemical impedance spectroscopy, and surface photovoltage spectroscopy analyses. Electron spin resonance spectroscopy indicated that h +, ·O2 –, and ·OH played dominant roles in the photocatalytic degradation of tetracycline. Liquid chromatography confirmed that, rather than being adsorbed, tetracycline was successfully photodegraded. Finally, an electron transfer mechanism for the generation of intermediates during tetracycline degradation was also proposed based on liquid chromatography-mass spectrometry and keto-enol tautomerism. These findings demonstrate the promising application of semiconductor/MOF heterojunctions as photocatalysts for pollutant degradation. Graphical abstract: Image 1 Highlights: 100NaBiO3 /UIO-67 achieves the degradation efficiencies of 88.6% for tetracycline (100 mg L -1 ). The electron transfer process is proposed based on theoretical study of Keto-Enol tautomerism. Liquid chromatography analysis further proves the degradation rather than adsorbed for tetracycline.